Description of Science Process Skills of Physics Education Students of Jambi University on Refraction Material on Concave Lenses Using E-Module - Irawati, Irawati; Putri Ningsi, Aziza (Integrated Science Education Journal, 2021)
Purpose of study: This study was conducted to determine the science process skills of physics education students for refraction material on a concave lens. The questions discussed in this study are to describe the basic and integrated science process skills of Jambi University physics education students, what are the obstacles faced when the implementation of the e-module basic physics practicum II is applied, what are the solutions to the obstacles faced. Methodology: This study uses a quantitative approach with descriptive methods. This research was conducted in the Physics Education Laboratory of the Teacher Training and Education Faculty, Jambi University. The sample l in this study were 40 physics education students contracting basic physics II subjects. The sampling technique used in this study was a total sampling technique. Main findings: With the use of a Manual for Basic Physics 1 practicum in the form of e-module, it can improve students' science process skills. It can be seen from the research results, that the science process skills of physics education students at Jambi University on refraction practicum material on concave lenses Novelty/Originality of this study: With this research, students are motivated to improve science process skills so that they become more active and more familiar with the concept of learning and can improve learning outcomes. Through this research, students can become more innovative and creative teachers, and can also find out the extent of students' science process skills.